Agree in restructuring: evidence from auxiliary switch and clitic climbing in French and Italian - Olivier, Marc (Springer Nature, 2026)
Auxiliary Switch (AS) is an under-studied phenomenon found in Romance restructuring clauses. It is contingent on the climbing of reflexive clitics, but sometimes remains insensitive to non-reflexive clitics. Drawing on the diachrony of French and comparative synchronic data from Italian and Sardinian, I argue that AS reflects a robust syntactic dependency between embedded and matrix domains, instantiated through Agree. The analysis adopts the hypothesis that auxiliary selection is governed not by argument structure but by person value identity. The main conclusions are that have is the default auxiliary in these languages, restructuring is not a phenomenon per se, and the locus of variation resides in the featural make-up of functional heads (cf. Borer-Chomsky Conjecture).
IN_PRESS
Keywords: agree; restructuring; auxiliary selection; romance syntax; french; italian; clitic climbing; syntax; Corpus Linguistics; LINGUISTICS; ROMANCE LINGUISTICS; Syntax